Vocabulary Learning Strategies : Shereen Ong Lee Jing A Case Study On Engineering Undergraduates Of Public And Private Universities - Ong, Shereen Lee Jing (Universiti Malaysia Sarawak (UNIMAS), 2017)
The study aimed to compare the vocabulary learning strategies (VLS) used by undergraduates engineering students from private and public universities. The objectives of the study are: 1) to examine the most frequently used VLS by students; 2) to compare the most frequently used VLS by male and female students; 3) to compare the differences in VLS used by students according to proficiency level. A total of 138 engineering students participated in the study. The two instruments used to collect data were Nelson English Language Proficiency Test (Version 300D) and Schmitt's (1997) Vocabulary Learning Strategies Questionnaire. The findings showed the most frequently used VLS was determination strategies whereas individual VLS were guessing the word's meaning from context, using Internet to search the word's meaning, remembering the word sounds and using English language media. For gender, memory and social strategies in the five categories of VLS were found to have significant difference. Intermediate students from public university also depicted significant difference in individual VLS use. For proficiency, there was no significant difference found in the use of determination, social and metacognitive strategies but there was significant difference shown in the use of memory and cognitive strategies. Significant differences were also identified in the use of seven similar individual VLS by students.